Design and optimization of topical terbinafine hydrochloride nanosponges: Application of full factorial design, in vitro and in vivo evaluation - Reham I Amer; Ghada H El-Osaily; Sameh S Gad (Wolters Kluwer Medknow Publications, 2020)
Terbinafine hydrochloride (THCl) has a broad-spectrum antifungal activity. THCl has oral bioavailability 40%, which increases dosing frequency of the drug, thus leads to some systemic side effects. Sustained release THCl nanosponges hydrogel was fabricated to deliver the drug topically. Pure THCl (drug), polyvinyl alcohol (emulsifier), and ethyl cellulose (EC, polymer to produce nanosponges) were used. THCl nanosponges were produced successfully by the emulsion solvent evaporation method. Based on a 32 full factorial design, different THCl: EC ratios and stirring rates were used as independent variables. The optimized formula selected based on the particle size and entrapment efficiency % (EE) was formulated as topical hydrogel. All formulations were found in the nanosize range except F7and F9. EE was ranged from 33.05% to 90.10%. THCl nanosponges hydrogel released more than 90% of drug after 8 h and showed the highest in vivo skin deposition and antifungal activity. The increase in drug: EC ratio was observed to increase EE and the particle size while higher stirring rate resulted in finer emulsion globules and significant reduction in EE. The drug release profile was slow from dosage form when it was incorporated in entrapped form as nanosponges rather than unentrapped one. The nanosponges hydrogel succeeded to sustain THCl release over 8 h. It showed the highest antifungal activity and skin deposition. THCl nanosponges hydrogel represents an enhanced therapeutic approach for the topical treatment of fungal infection.